Metabolic syndrome and infertility in men. Issue 4 (May 2015) - Morrison, Christopher D.; Brannigan, Robert E.
Abstract : Metabolic syndrome is a compilation of symptoms including central obesity, insulin resistance, dyslipidemia, and hypertension. Initially used to predict cardiovascular disease, it is now clear that the molecular and physiologic abnormalities seen in metabolic syndrome extend well beyond the cardiovascular system. Growing evidence has linked metabolic syndrome and its individual symptoms to the increasing prevalence of male infertility. This manuscript reviews the recent evidence connecting metabolic syndrome to male infertility as well as the underlying pathophysiology. Currently, there are limited prospective studies examining the effects of treating metabolic syndrome on male reproduction and these relationships will need to be a focus of further investigation. Highlights: Metabolic syndrome is a compilation of symptoms including central obesity, insulin resistance, dyslipidemia, and hypertension. The molecular and physiologic abnormalities seen in metabolic syndrome extend well beyond the cardiovascular system. Growing evidence has linked metabolic syndrome and its individual symptoms to the increasing prevalence of male infertility. We review the recent evidence connecting metabolic syndrome to male infertility as well as the underlying pathophysiology.